Caffeine prevents transcription inhibition and P-TEFb/7SK dissociation following UV-induced DNA damage. - Giuliana Napolitano; Stefano Amente; Virginia Castiglia; Barbara Gargano; Vera Ruda; Xavier Darzacq; Olivier Bensaude; Barbara Majello; Luigi Lania (PLoS ONE, 2010)
Background The mechanisms by which DNA damage triggers suppression of transcription of a large number of genes are poorly understood. DNA damage rapidly induces a release of the positive transcription elongation factor b (P-TEFb) from the large inactive multisubunit 7SK snRNP complex. P-TEFb is required for transcription of most class II genes through stimulation of RNA polymerase II elongation and cotranscriptional pre-mRNA processing. Methodology/principal findings We show here that caffeine prevents UV-induced dissociation of P-TEFb as well as transcription inhibition. The caffeine-effect does not involve PI3-kinase-related protein kinases, because inhibition of phosphatidylinositol 3-kinase family members (ATM, ATR and DNA-PK) neither prevents P-TEFb dissociation nor transcription inhibition. Finally, caffeine prevention of transcription inhibition is independent from DNA damage. Conclusion/significance Pharmacological prevention of P-TEFb/7SK snRNP dissociation and transcription inhibition following UV-induced DNA damage is correlated.